1997
DOI: 10.1128/mcb.17.11.6508
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Serine Phosphorylation by ERK-Dependent and -Independent Pathways Negatively Modulates Its Tyrosine Phosphorylation

Abstract: Recent studies have indicated that serine phosphorylation regulates the activities of STAT1 and STAT3. However, the kinase(s) responsible and the role of serine phosphorylation in STAT function remain unresolved. In the present studies, we examined the growth factor-dependent serine phosphorylation of STAT1 and STAT3. We provide in vitro and in vivo evidence that the ERK family of mitogen-activated protein (MAP) kinases, but not JNK or p38, specifically phosphorylate STAT3 at serine 727 in response to growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
524
8
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(580 citation statements)
references
References 42 publications
(59 reference statements)
45
524
8
3
Order By: Relevance
“…As a control, blots were stripped and reprobed with gated. Previous reports have indicated that IL-6-induced STAT3 Ser(#( phosphorylation is an ERK-1-independent process [41,50], and we have been able to confirm these results in HepG2 cells. Blocking ERK activation by overexpression of dominant-negative Raf, N∆Raf [46], or by using the MEK inhibitor PD09859 did not alter STAT3 Ser(#( phosphorylation or transactivation (results not shown).…”
Section: Figure 2 Il-6 Does Not Activate Jnk-1 In Hepg2 Cellssupporting
confidence: 87%
See 1 more Smart Citation
“…As a control, blots were stripped and reprobed with gated. Previous reports have indicated that IL-6-induced STAT3 Ser(#( phosphorylation is an ERK-1-independent process [41,50], and we have been able to confirm these results in HepG2 cells. Blocking ERK activation by overexpression of dominant-negative Raf, N∆Raf [46], or by using the MEK inhibitor PD09859 did not alter STAT3 Ser(#( phosphorylation or transactivation (results not shown).…”
Section: Figure 2 Il-6 Does Not Activate Jnk-1 In Hepg2 Cellssupporting
confidence: 87%
“…Possibly, p38 squelches the activity of an upstream kinase like SEK-1\MKK-4, which is blocked in the presence of SB203580. This hypothesis is supported by recent results, showing that SEK-1\MKK-4 is indeed capable of binding and activating p38 [29,50] and that p38 has an inhibiting effect on JNK-1-mediated Elk activation [33]. Whether the effects of SB203580 on STAT3 transactivation involve cross talk between the p38 and SAPK\JNK pathways requires further investigation.…”
Section: Discussionmentioning
confidence: 56%
“…EGF alone also increased the phosphorylation and nuclear uptake of MAPK ; the effect of EGF on MAPK was enhanced by T % . STAT3 has been shown by others to undergo Serine-727 phosphorylation by the MAPK pathway [23], as well as by a mechanism independent of that pathway [7]. This serine phosphorylation has been regarded as essential for maximal transcriptional activity of STAT3 [6].…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated by EGF, STAT3 is tyrosine-phosphorylated at residue 705 and translocates to the nucleus, either as a homodimer or as a heterodimer with the 91 kDa STAT1α, where it binds to selected EGF-responsive DNA sequences [5]. STAT3 and STAT1α both contain a C-terminal serine residue (residue 727) that is subject to phosphorylation by the mitogen-activated protein kinase (MAPK) pathway [6,7], as well as by other serine kinases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Equal amounts of nuclear extracts were subjected to mobility shift analysis using the hSIE (upper panel) or Ie (lower panel) probe expressing CSF/PDGF receptors. MAP kinases have been implicated in phosphorylation of STAT proteins on serine and thereby regulating transactivation by and tyrosine phosphorylation of STATs (Wen et al, 1995;Chung et al, 1997). Activation of the MAP kinases ERK1 and ERK2 was inferred from the appearance of electrophoretically-retarded, phosphorylated forms (Anderson et al, 1990).…”
Section: Activation Of Map Kinase and C-fos Rna Accumulation By Csf/pmentioning
confidence: 99%